2015
DOI: 10.3390/ijms160921035
|View full text |Cite
|
Sign up to set email alerts
|

A Series of New Ligustrazine-Triterpenes Derivatives as Anti-Tumor Agents: Design, Synthesis, and Biological Evaluation

Abstract: A series of novel ligustrazine-triterpenes derivatives was designed, synthesized and screened for their cytotoxicity against five cancer cell lines (Bel-7402, HepG2, HT-29, Hela, and MCF-7) and Madin-Darby canine kidney (MDCK). Current study suggested that most of the ligustrazine-triterpenes conjunctions showed better cytotoxicity than the starting materials. In particular, compound 4a exhibited better cytotoxic activity (IC50 < 5.23 μM) against Bel-7402, HT-29, MCF-7, Hela, and HepG2 than the standard antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…As shown in Scheme 1 , Scheme 2 , Scheme 3 and Scheme 4 , all the designed derivatives were synthesized [ 20 , 24 ]. In Scheme 1 , six kinds of chloromethyl pyrazines were produced by N -chlorosuccinimide (NCS) and benzoyl peroxide (BPO) in carbon tetrachloride (CCl 4 ) under light conditions with nitrogen protection, and the yield ranged from 40–60%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Scheme 1 , Scheme 2 , Scheme 3 and Scheme 4 , all the designed derivatives were synthesized [ 20 , 24 ]. In Scheme 1 , six kinds of chloromethyl pyrazines were produced by N -chlorosuccinimide (NCS) and benzoyl peroxide (BPO) in carbon tetrachloride (CCl 4 ) under light conditions with nitrogen protection, and the yield ranged from 40–60%.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrazine is an N -heteroaromatic ring, and the incorporation of N -heteroaromatic rings into organic molecules could improve their antitumor activity and aqueous solubility [ 10 , 22 , 23 ]. Our research group proved that the introduction of ligustrazine to betulinic acid, ursolic acid, glycyrrhetinic acid, and oleanolic acid could significantly improve their antitumor effects in vitro [ 24 , 25 ]. Among them ( Figure 1 ), compound 3β-hydroxyolea-12-en-28-oic acid-3,5,6-trimethylpyrazin-2-methyl ester (I), 3β-hydroxyurs-12-en-28-oic acid-3,5,6-trimethylpyrazin-2-methyl ester (II), and 3β-hydroxy-lup-20(29)-ene-28-oic acid-3,5,6-trimethylpyrazin-2-methyl ester (III) exhibited significant cytotoxicity against a variety of tumor cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis was initiated by oxidation of ligustrazine 1 with hot KMnO 4 solution to afford 3,5,6-trimethylpyrazine-2-carboxylic acid 2. 19 Then, carboxylic acid 2 underwent coupling with p-aminobenzoic acid 3a, p-aminophenylacetic acid 3b, and m-aminobenzoic acid 4 via 1ʹ-carbonyldiimidazole (CDI) to furnish the key intermediates 4a,b and 6, respectively. Then, the target ligustrazinebased HDACIs (7a-c and 8a, b) were obtained, with 45-60% yield, via coupling of key intermediates 4a,b and 6 with hydrazine hydrate or hydroxylamine by the use of CDI (Scheme 1).…”
Section: Results and Discussion Chemistrymentioning
confidence: 99%
“…15,16 Accordingly, ligustrazine has attracted considerable attention as a privileged scaffold in cancer drug discovery. In this context, several studies reported the development of different ligustrazine-based hybrids such as ligustrazine-curcumin hybrids, 17,18 ligustrazine-terpenes hybrids 19 and others. 20,21 The aforementioned findings have inspired and guided us to design and synthesize a new set of HDAC inhibitors (7a-c and 8a,b) utilizing ligustrazine as a novel cap moiety, and achieving the pharmacophoric features required to induce the desired inhibition ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Many effective bivalent anti-cancer drugs have been found, such as artemisinin-derivative dimers [10], jesterone dimer [11], indole-3-carbinol dimer [12], bis-daunorubicin [13]. Previous work in this field has designed and synthesized several ligustrazine dimers linked by cyclohexanone and oxime [14], curcumin [15], or triterpenes [16], which had a good cytotoxic effect on human cancer cells. The result showed that the dimerization of ligustrazine could obviously improve the antitumor potency of its monomer.…”
Section: Introductionmentioning
confidence: 99%